(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2015)
One of the strategic projects initiated in Europe in the period 2011-2014 was the project DARIAH-EU which had the main goal to elevate research in Humanities and Arts science using digital technologies and create special infrastructure across Europe. Czech Republic is in the phase of joining this infrastructure. Digital Humanity is a new scientific discipline which appeared in the last decade in many universities over the world and spread into many directions. We joined this activity in the field of performing arts. Our objective was to verify whether modern computer network and audio-visual technologies can enable collaborative work of performing artists when they are distributed across large distances and what are the requirements and limitations. We will describe our experience from the events which we organized or on which we participated during the last 4 years in Europe, US, Malaysia, Korea and Taiwan. The experiments showed that Global Performances as new form of performing arts can be arranged for different type of artists. The GP bring new very interesting impressions for artists and for the spectators. We demonstrated that GP can be used for presentation of performing arts on the festivals, cultural exhibitions and fairs. We believe that, It could have very positive economic effect. It is our IT contribution to Digital Humanities and Arts. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.